Ethical dimensions of current issues regarding safe blood donation - Tint, Khin San (My University, 2008)
ABSTRACT In the HIV/AIDS literature, a perspective that has not received a great amount of attention concerning blood donation per se and the duties and obligations of Blood Transfusion Services (BTS)i when held to the question of fairness raised by socially marginalised persons (or groups) who altruistically wish to donate blood in the face of the HIV/AIDS pandemic is addressed in this research report. The represented marginalised group I use is Men who have Sex with Men (MSM)ii Acquired Immunodeficiency Syndrome, commonly called AIDS first came to the attention of the public in the 1980s. From an unknown unnamed emerging infectious diseaseiii ,it has grown into a pandemic familiar to all. Primarily transmitted either sexually or via contaminated needles, the HIV infected individual is initially an asymptomatic carrier. Once an individual Once an individual is infected with the virus, he or she can pass it on to others by way of body fluids, e.g. blood and semen. HIV, whether treated or not, will eventually develop into AIDS for which there is currently no known cure. AIDS is uniformly mortal. i In this research report, I will refer to the industry as “Blood Transfusion Services” although in some countries it is referred to as “Blood Bank Services” ii Men who have Sex with Men (MSM) according to the London-based PANOS Institute include men who have sex with both men and women, men who have sex with only other men, men who have sex with boys and men, male sex workers and their clients, male transvestites and transsexuals, male street children and men in prison (McKenna 1999:1) iii As defined by Lashley, F, (2006) Emerging Infectious Diseases are ‘diseases of infectious origin whose incidence in humans has increased within the past two decades or threatens to increase in the near future’ The media abounds with literature concerning HIV/AIDS looking at it from various perspectives. iv Moreover, and correctly, in South Africa we are knowledgeable that what once was considered as a threat only to homosexualsv or IV drug users – individuals marginalised by their nonconformance to society’s norms – is now epidemiologically a disease spread in our society primarily by non-drug using heterosexuals. The tension between promoting the public good in the face of an pandemic while simultaneously protecting against unjust discrimination against individuals or groups represents an ethical dilemma faced by all public health organisations including BTS. Principally contextualised in iv e.g. clinical research in, guidelines pertaining to, ethical issues about, legal precedents concerning, duties of medial personnel towards, epidemiological analysis, psychological monitoring …and so on. v At the end of the 19th century, homosexuality was profiled as a mental illness by the German psychiatrist Richard von Krafft-Ebing in his reference book Psychopathis Sexualis.v In the absence of scientific evidence to prove otherwise, this view became widely accepted . Eventually, many different societies perceived homosexuals including MSM as unstable and this reinforced discriminatory practices against them. v Even today, the harmful consequences of homophobia impact on MSM in many different ways. Meyers describes three negative conditions or practices common to the experience of MSM. They are: the internalisation of homophobia to the extent that they accept rejection from society; the experience of social stigmatisation; and overt discrimination and violence.v From some religious aspects, homosexuality is considered a “sin against nature” and is often seen as a link to AIDS, which is again seen as God’s punishment for a “life against nature”.v The Koran suggests punishment for those involved in homosexual acts on the basis of harm to society, and Sharia law admits no tolerance towards homosexuality.v. Predominantly Catholic Latin American countries enforce socio-cultural and legal restrictions to prohibit homosexuality. (Mckenna 1999:11) From Buddhist perspective, homosexuals are not permitted to become a monk and to practice through monk-hood the ultimate goal of attaining the highest level of enlightenment (Nirvana) (Ven Chanmyay Sayadaw Janakabhivamsa 1997:9 ). However, they are as equal as are others when following the paths taken that may lead them to attain Nirvana (Personal communication with Ven Ashin Manijoti, Theravada Buddhist Dhammodaya Monastery, Pietermaritzburg). the milieu of South Africa but practiced globally, the responsibility of BTS’s may broadly be grouped into two areas: 1) the provision of blood & its products to a given population based upon their estimated need; and 2) the assurance of blood and blood-product safety. While these may be considered only technical issues, they are not so clear-cut. Rather, they include conflicts of values and social-political agendas. Historically, BTSs have used discriminatory practices to exclude certain groups from blood donation. Independent of country or nation and in spite of advancements in blood screening science, the existent social-political order has influence on the policies and practices of BTSs such as the separation of groups into “high-risk” and ”low risk” blood donor categories. On the surface, such separations may appear to be straightforward scientific and prudential public health policy. However, when one considers the most common manner of HIV transmission - as occurring during intimate sexual acts which take place within society’s emphasis on private and individual rights but when such acts are considered by society to be ‘deviant ‘ - one might ask how the terms high- and low- risk are influenced by societal perceptions of the group in question. In other words, I suggest that societal (including political, religious, and economic) perceptions of a marginalised group’s private sexual acts influence public health policy; private acts have social consequences. Weighing the pros and cons of ethical arguments, this research report concludes that because of advanced blood transfusion science, it is morally justifiable to accept blood from all altruistic competent adult individuals volunteering to donate. Moreover, in this regard, it is the duty of BTS to safeguard the national blood supply by means other than excluding marginalised groups. To do otherwise is ethically unwarranted and constitutes unfair discrimination. In addition, through identifying that the act of blood donation is based on altruism or the “gift relationship,” the exclusion of marginalised groups from altruistic blood donation, serves only to further excludes them from an act, which is in essence humanitybinding. That being said, to achieve this end, all altruistic competent adults who wish to donate blood are obliged to understand the purpose, nature, and duties BTS’s have and adopt a renewed sense of social responsibility broadening our vision of the public good..
Keywords: safe blood donation; ethics; msm; gift relationship